The five year survival of women with cervical cancer in Metro Manila and the Rizal Province - Redaniel, Maria Theresa (2000)
Cancer of the cervix ranks as the second most common neoplasms among women. It is the fourth most common cancer site among both sexes with lung cancer ranking first, breast second and liver third. Moreover, cervical carcinoma ranks as the sixth cause of cancer deaths for both sexes, and the third among women next to breast and lung.A retrospective cohort study was done through a review of the records of the Philippine Cancer Society-Manila Cancer Registry (PCS-MCR) and the Department of Health-Rizal Cancer Registry (DOH-RCR). Four hundred sixty-seven women were diagnosed to have cervical cancer in the Metro Manila and Rizal area in 1987. A survival analysis was conducted on 202 cases, the purpose of which was to determine the five-year survival experience of women and to identify the factors associated with survival.The findings of the study indicated that the median survival time of these women was 44.97 months with an observed survival of only 33.3. This was lower than most developing and developed countries. Furthermore, of the factors studied-age, stage and histology, only stage at the time of diagnosis had a significant effect on survival. The earlier the stage at the time of presentation, the better the prognosis. Women diagnosed to have stage II and stage III or IV were 3.2 and 4.7 times, respectively, more at risk of dying than those with stage 0 or I. This gives emphasis on the importance of screening programs to detect early stage tumors and therefore increase survival.
Thesis (MS Epidemiology)--University of the Philippines Manila.
Keywords: Cervix uteri -- Cancer; Cervical cancer